Why Nigeria Must Strengthen its Local Pharmaceutical Manufacturing Capacity - Melody Okereke; Adebowale Adekunbi; Yusuf Ghazali (University of Minnesota Libraries Publishing, 2021)
With over 115 registered pharmaceutical manufacturers, Nigeria still depends on other countries for the supply of active pharmaceutical ingredients and excipients. Significant attention has not been paid to the local production of raw materials, pharmaceutical dosage formulations, or processing equipment, which has resulted in a decline in the country's pharmaceutical manufacturing capacity. Owing to the overall importance of the pharmaceutical industry, it is, therefore, essential to pay close attention to developmental issues affecting this sector. In this commentary, we explore why Nigeria must boost its local pharmaceutical manufacturing capacity.